Othered flesh : social-scientific and critical patial investigations into the tattooed ancient near eastern body as space and body in space - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.